A cluster analysis of epidemiological and clinical factors associated with the accumulation process of the burden of COVID-19 in European countries - Shojaee, Sajad; Eslami, Pegah; Dooghaie Moghadam, Arash; Pourhoseingholi, Mohamad Amin; Ashtari, Sara; Vahedian-Azimi, Amir; Zali, Mohammad Reza (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the workEuropean COVID-19 statistics showed differentiation between mortality and new cases. Some studies suggested several factors including migration, cancer incidence, life expectancy and health system capacity maybe associated with differentiations. Up to now, impact of those factors in different European societies is not discussed and compared. Aim of the present study was to perform the cluster analysis in European countries in attention to clinical and epidemiological factors due to covid-19.MethodsWe collected some appropriate extreme data of COVID-19 to access the situations by ANOVA post-hoc test in 3 scenarios, as well as to estimate regression coefficients in simple linear regression, and a cluster analysis using average linkage. Covid-19 Statistics were considered in all analyses until April 24, 2020.ResultsAmong 39 European countries, several countries reported highest rate of confirmed cases included of Italy (current statues=2270.52) and Spain (current status=2616.24). The highest rate of mortality was seen in France (current status=242.16), Italy (current status=305.52). Life expectancy (female) (P=0.01, 95%Cl=1521.27,15264.58), migration (P